Chlorine Dioxide Oxidation in Water Treatment: Impact on Natural Organic Matter Characteristics, Disinfection Byproducts and Comparison with Other Oxidants - Rougé, Valentin Roland (Curtin University, 2018)
Disinfection during water treatment can lead to the formation of unwanted disinfection byproducts (DBPs) arising from the reaction of the disinfectant and the Natural Organic Matter (NOM). Pre-treatment such as pre-oxidation can be applied to reduce the formation of DBPs. This Thesis presents an improved understanding of the mechanisms and the impact of pre-oxidation on NOM characteristics when chlorine dioxide (ClO2) is used as a pre-treatment, and its DBP reduction efficiency compared with other oxidants.